Trophic relations based on fecal DNA in tundra terrestrial food webs near Kongsfjorden, Svalbard, Norway - Kim, Jihee; Lee, Won Young; Park, Sangkyu (Polar Biology, 2022)
For the conservation and management of the Arctic regions vulnerable to climate change, it is important to elucidate the trophic relations and food sources for consumers in the ecosystems. We analyzed DNA extracted from feces to understand the summer diets of the major terrestrial animals and their trophic relations in tundra ecosystems near Kongsfjorden, Svalbard. Feces of Svalbard reindeer (Rangifer tarandus platyrhynchus), Barnacle Goose (Branta leucopsis), Arctic fox (Vulpes lagopus), and Rock Ptarmigan (Lagopus muta) were collected during the summer seasons of 2014, 2015, 2018, and 2019. Plant DNA was detected in the feces of herbivores (reindeer, goose, and ptarmigan) and vertebrate DNA was detected in the feces of carnivore (Arctic fox) by amplifying, cloning, and Sanger sequencing. In case of Arctic fox, VulpesB, the blocking primer preventing from amplifying Arctic fox DNA, was used to improve the detection of their prey DNA. Salix was the most detected genus in feces of Svalbard reindeer and Barnacle Goose, which were described as feeding on graminoids, forbs, and prostrate as well as bryophyte. Bryophyte was added as an important food source for all herbivores. Arctic fox preferred birds such as geese (Anatidae) and gulls (Laridae), showing that interpretation between Arctic foxes and gulls may have occurred at the same predator level. Our results suggest that cloning-based DNA analysis using fecal sample contributes to understanding the tundra terrestrial food web near Kongsfjorden.
Keywords: Arctic food webs; Arctic fox; Barnacle Goose; Fecal dietary analysis; Svalbard; Svalbard reindeer